Pengaruh Personality Traits, Congruity, Dan Online Customer Review Terhadap Customer Retention Dengan Customer Satisfaction Sebagai Variabel Mediasi Pada Generasi Z Di Coffee Shop Surabaya - Faiz Bahalwan; Sri Setyo Iriani; Yessy Artanti (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the influence of personality traits, congruity, and online customer reviews on customer retention, both directly and indirectly, with customer satisfaction as a mediating variable. This research design uses a quantitative approach with an explanatory research type. The study was conducted in Surabaya City with 220 Generation Z coffee shop consumers as subjects. The data analysis technique used Structural Equation Modeling (SEM). The results show that personality traits, congruity, and online customer reviews influence customer retention, both directly and indirectly, with customer satisfaction as a mediating variable. Suggestions for coffee shop managers are to actively manage and provide feedback regarding consumer assessments through platforms such as Google Review, Instagram, and TikTok.